A silicon composite material and its preparation method and application
By coating the surface of the silicon substrate with highly conductive compounds Nb2S2C and Ta2S2C, the problems of low energy density and poor conductivity of lithium-ion anode materials are solved, and the high specific energy and excellent electrochemical performance of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202211012383.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-23
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-08-23
AI Technical Summary
The existing lithium-ion anode materials have problems with low energy density, poor conductivity and rate performance.
By coating the surface of the silicon substrate with compounds such as Nb2S2C and Ta2S2C, its high conductivity and layered two-dimensional structure can be used to improve the conductivity and rate performance of the negative electrode material.
It significantly improves the specific energy, rate performance and conductivity of lithium-ion batteries, ensuring the energy density and cycle performance of the anode material.
Smart Images

Figure CN115483373B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a silicon composite material and a preparation method and application thereof. Background Art
[0002] With the increasing popularity of new energy vehicles, lithium-ion batteries have attracted widespread attention in the field of power batteries due to their high operating voltage, no memory effect, low self-discharge, high energy density and long cycle life. At present, power lithium-ion batteries are mainly developed in the direction of high energy density, low production cost and high safety, which also leads to higher and higher requirements for electrode materials. In particular, negative electrode materials are an important component of batteries. The theoretical capacity of commercial graphite negative electrode materials is 372mAh / g, which can no longer meet the capacity matching requirements of high-energy positive electrode materials such as lithium-rich materials and nickel-manganese spinel high-voltage materials.
[0003] In recent years, a class of silicon-based materials with ultra-high capacity (theoretical capacity of 4200mAh / g) as a large and abundant resource is considered to be an ideal material to replace graphite negative electrodes. However, studies have found that silicon negative electrode materials will undergo a dramatic volume expansion (0-300%) during the lithium insertion and extraction reaction, resulting in structural damage and pulverization of the electrode material, resulting in defects such as rapid capacity decay and shortened cycle life.
[0004] Studies have shown that the volume expansion rate of silicon oxide during lithium insertion and extraction is significantly lower than that of silicon negative electrode materials. This is because silicon oxide generates inert Li when it is first inserted into lithium. 2 O and Li 4 SiO 4 , thus effectively alleviating the volume expansion effect, so the use of silicon oxide as the negative electrode material has better cycle performance. Although the cycle performance of silicon oxide is improved compared to silicon, its conductivity and rate performance are still difficult to meet the requirements of practical applications.
[0005] CN114361427A discloses a method for coating silicon negative electrode materials with carbon nanotubes, specifically, a method for coating the surface of silicon oxide with a layer of carbon nanotubes, and utilizing the strong conductivity of the carbon nanotube coating layer itself to increase the conductivity and rate performance of the negative electrode silicon oxide body. The defects of this method are: due to the tubular hollow structure of the carbon nanotubes themselves, it is impossible to achieve uniform coating, and the large shrinkage of silicon oxide itself during the charge and discharge process will destroy the carbon nanotube structure, thereby affecting the subsequent conductivity of silicon oxide. Summary of the invention
[0006] The purpose of the present invention is to provide a silicon composite material and a preparation method and application thereof, so as to solve the problems of low energy density, poor conductivity and rate performance of existing lithium ion negative electrode materials.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A silicon composite material comprises a substrate, the surface of which is coated with a compound;
[0009] The substrate is selected from one or more of silicon, silicon carbide and silicon monoxide, and the compound is selected from Nb 2 S 2 C and Ta 2 S 2 One or both of C.
[0010] According to the above technical means, by coating the surface of the silicon substrate with a compound, the compound is selected from Nb 2 S 2 C and Ta 2 S 2 One or two of C, Nb 2 S 2 C and Ta 2 S 2 C have high conductivity. After coating on the surface of silicon substrate, the conductivity of silicon composite material is improved. 2 S 2 C and Ta 2 S 2 C itself is a layered two-dimensional structure with a large interlayer spacing. After being coated on the surface of the silicon substrate, it is used as the negative electrode material of the lithium-ion battery, which facilitates the rapid insertion and extraction of lithium ions, thereby improving the rate performance of the silicon composite material. At the same time, it was also found that Nb 2 S 2 C and Ta 2 S 2 C itself has a high lithium storage performance (specific capacity > 400mAh / g). After being coated on the surface of the silicon substrate, the overall specific capacity can still be maintained at 400mAh / g, thereby effectively ensuring the energy density of the negative electrode material and expanding the applicability of the negative electrode material.
[0011] Preferably, the substrate is selected from silicon dioxide, and the compound is a single layer of Nb 2 S 2 C and / or Ta 2 S 2 C.
[0012] Since silicon oxide has better cycle performance than other silicon substrates, and due to the multi-layer Nb 2 S 2 C and / or Ta 2 S 2The interlayer spacing of C is relatively small, and after being coated on the surface of the substrate, the lithium insertion property is poor. Therefore, silicon dioxide is selected as the substrate, and a single layer of Nb 2 S 2 C and / or Ta 2 S 2 Composite materials made of C as coating material can further improve rate performance and cycle performance.
[0013] Preferably, the mass ratio of the compound to the substrate is 0.1:99.9 to 3:17.
[0014] By controlling the mass ratio of the compound to the substrate, the electrochemical performance of the composite material is effectively guaranteed.
[0015] Preferably, the particle size of the substrate is between 2 and 800 nm.
[0016] The present invention also provides a method for preparing the silicon composite material of the present invention, comprising the following steps:
[0017] The compound is dissolved in a solvent, subjected to ultrasonic treatment, then added to a substrate, and dried to obtain an intermediate;
[0018] The intermediate is placed in an inert atmosphere, heated at 700-1200° C. for 0.5-6 hours, and cooled to obtain a silicon composite material.
[0019] According to the above technical means, by dissolving the compound in a solvent and performing ultrasonic treatment, the compound is evenly dispersed in the solvent and forms a monolayer molecular structure, which provides the prerequisite for uniform coating of the silicon substrate; at the same time, ultrasonic treatment is performed after adding the substrate to further ensure that the compound is evenly coated on the surface of the silicon substrate.
[0020] Preferably, the intermediate is heated in an inert atmosphere at a temperature of 800° C. for 3.5 hours.
[0021] By setting the heating temperature to 800°C and the time to 3.5 h, effective coating of the compound was ensured.
[0022] Preferably, the ultrasonic treatment time is 0.5 to 6 hours;
[0023] The drying temperature is 80°C to 200°C.
[0024] The time of ultrasonic treatment is controlled between 0.5 and 6 h to make the compound uniformly dispersed in the solvent.
[0025] Preferably, the ultrasonic treatment time is 2 h.
[0026] Preferably, the solvent is selected from one or more of deionized water, anhydrous ethanol, acetone, dimethylformamide and tetrahydrofuran.
[0027] By selecting deionized water, anhydrous ethanol, acetone, dimethylformamide and tetrahydrofuran as solvents, the uniformity of compound dispersion is effectively guaranteed.
[0028] Preferably, the inert gas in the inert atmosphere is selected from one or more of nitrogen, helium, argon and hydrogen.
[0029] The present invention also provides application of the silicon composite material of the present invention, wherein the silicon composite material is used as a negative electrode material of a lithium ion battery.
[0030] According to the above technical means, by using silicon composite materials as negative electrode materials of lithium-ion batteries, the specific energy, rate performance and conductivity of lithium batteries can be significantly improved.
[0031] Beneficial effects of the present invention:
[0032] 1) The silicon composite material of the present invention comprises a compound coated on the surface of a silicon substrate, wherein the compound is selected from Nb 2 S 2 C and Ta 2 S 2 One or two of C, Nb 2 S 2 C and Ta 2 S 2 C has high conductivity. After coating on the surface of silicon substrate, it improves the conductivity of negative electrode material. 2 S 2 C and Ta 2 S 2 C, with a large interlayer spacing, is used as the negative electrode material of lithium-ion batteries after being coated on the surface of the silicon substrate, which facilitates the rapid insertion and extraction of lithium ions, thereby improving the rate performance of the negative electrode material; at the same time, it was also found that Nb 2 S 2 C and Ta 2 S 2 C itself has a high lithium storage performance (specific capacity> 400mAh / g). After being coated on the surface of the silicon substrate, the overall specific capacity remains above 400mAh / g, which effectively guarantees the energy density of the negative electrode material and expands the applicability of the negative electrode material.
[0033] 2) The method for preparing the silicon composite material of the present invention is to dissolve the compound in a solvent and perform ultrasonic treatment so that the compound is uniformly dispersed in the solvent and forms a monolayer of molecules, which provides a prerequisite for uniform coating of the silicon substrate, and has the advantages of simple process, low cost, and conducive to large-scale commercial application;
[0034] 3) The negative electrode material of the present invention is used to make the negative electrode material of lithium battery, which has the advantages of high specific energy, good rate performance and excellent electrochemical performance, and has the value of promotion and application in the field of lithium ion battery technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 For a single layer of Nb 2 S 2 Schematic diagram of the atomic structure of C;
[0036] Figure 2 This is a transmission electron microscope image of the silicon composite material prepared in Example 1. DETAILED DESCRIPTION
[0037] The following will describe the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.
[0038] It should be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present invention, and thus the drawings only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0039] In the following description, numerous details are discussed to provide a more thorough explanation of the embodiments of the present application. However, it is obvious to those skilled in the art that the embodiments of the present application can be implemented without these specific details.
[0040] Example 1
[0041] A method for preparing a silicon composite material comprises the following steps:
[0042] S1, 0.1g Nb 2 S 2 C was dissolved in deionized water and subjected to ultrasonic treatment at room temperature for 3 h to obtain a single layer of Nb 2 S 2 Solution C;
[0043] S2, add 99.9g of silicon oxide to the monolayer of Nb 2 S 2 C (such as Figure 1 The mixture was mixed evenly in a solution as shown, and then placed in an oven at 100° C. to dry to obtain an intermediate;
[0044] S3. The intermediate is placed in a furnace under the protection of argon gas, heated to 900°C and kept warm for 5 hours. After the temperature is naturally cooled and impurities are removed, a silicon composite material is obtained.
[0045] Example 2
[0046] A method for preparing a silicon composite material comprises the following steps:
[0047] S1, 10g Nb 2 S 2 C was dissolved in deionized water and subjected to ultrasonic treatment at room temperature for 4 h to obtain a single layer of Nb 2 S 2 Solution C;
[0048] S2, add 90g of silicon oxide to the monolayer of Nb 2 S 2 C solution, mix well, and then place in an oven at 90°C to dry to obtain an intermediate;
[0049] S3. The intermediate is placed in a furnace under the protection of argon gas, heated to 1000° C. and kept warm for 6 hours. After the temperature is naturally cooled and impurities are removed, a silicon composite material is obtained.
[0050] Example 3
[0051] A method for preparing a silicon composite material comprises the following steps:
[0052] S1, 5g Nb 2 S 2 C was dissolved in deionized water and subjected to ultrasonic treatment at room temperature for 6 h to obtain a single layer of Nb 2 S 2 Solution C;
[0053] S2, add 95g of silicon oxide to the monolayer of Nb 2 S 2 C solution, mix well, and then place in an oven at 120°C to dry to obtain an intermediate;
[0054] S3. The intermediate is placed in a furnace under argon protection, heated to 1100° C. and kept warm for 6 hours. After the temperature is naturally cooled and impurities are removed, a silicon composite material is obtained.
[0055] Example 4
[0056] A method for preparing a silicon composite material comprises the following steps:
[0057] S1, 5g Nb 2 S2 C was dissolved in deionized water and subjected to ultrasonic treatment at room temperature for 6 h to obtain a single layer of Nb 2 S 2 Solution C;
[0058] S2, add 95g silicon to the monolayer Nb 2 S 2 C solution, mix well, and then place in an oven at 120°C to dry to obtain an intermediate;
[0059] S3. The intermediate is placed in a furnace under argon protection, heated to 1100° C. and kept warm for 6 hours. After the temperature is naturally cooled and impurities are removed, a silicon composite material is obtained.
[0060] Example 5
[0061] A method for preparing a silicon composite material comprises the following steps:
[0062] S1, 5g Nb 2 S 2 C was dissolved in deionized water and subjected to ultrasonic treatment at room temperature for 6 h to obtain a single layer of Nb 2 S 2 Solution C;
[0063] S2, put 95g of silicon carbide into a single layer of Nb 2 S 2 C solution, mix well, and then place in an oven at 120°C to dry to obtain an intermediate;
[0064] S3. The intermediate is placed in a furnace under argon protection, heated to 1100° C. and kept warm for 6 hours. After the temperature is naturally cooled and impurities are removed, a silicon composite material is obtained.
[0065] Comparative Example 1
[0066] A method for preparing a silicon material comprises the following steps:
[0067] S1. Ultrasonic treatment of 50 ml of deionized water at room temperature for 3 h;
[0068] S2, adding 95g of silicon dioxide into 50ml of deionized water, and then drying in an oven at 120°C to obtain an intermediate;
[0069] S3. The intermediate is placed in a furnace under the protection of argon gas, heated to 1100° C. and kept warm for 6 hours. After the temperature is reached, the intermediate is naturally cooled to obtain a silicon material.
[0070] Comparative Example 2
[0071] A method for preparing a silicon material comprises the following steps:
[0072] S1. Ultrasonic treatment of 50 ml of deionized water at room temperature for 4 h;
[0073] S2, adding 95g of silicon into 50ml of deionized water, and then drying in an oven at 120°C to obtain an intermediate;
[0074] S3. The intermediate is placed in a furnace under argon protection, heated to 1100° C. and kept warm for 4 hours. After the temperature is reached, the intermediate is naturally cooled to obtain a silicon material.
[0075] Comparative Example 3
[0076] A method for preparing a silicon material comprises the following steps:
[0077] S1. Ultrasonic treatment of 50 ml of deionized water at room temperature for 3 h;
[0078] S2, adding 95g of silicon carbide into 50ml of deionized water, and then drying in an oven at 120°C to obtain an intermediate;
[0079] S3. The intermediate is placed in a furnace under the protection of argon gas, heated to 1100° C. and kept warm for 2 hours. After the temperature is reached, the intermediate is naturally cooled to obtain a silicon material.
[0080] Detection and analysis
[0081] 1. Transmission electron microscopy analysis
[0082] The silicon composite material prepared in Example 1 was analyzed by transmission electron microscopy. The results are as follows: Figure 2 shown.
[0083] from Figure 2 It can be seen from the analysis that the surface of silicon oxide is uniformly coated with Nb 2 S 2 C.
[0084] 2. Conductivity test
[0085] The electrical conductivities of the silicon composite materials prepared in Examples 1 to 5 and the silicon materials prepared in Comparative Examples 1 to 3 were measured using a Japanese Mitsubishi Chemical MCP-PD51 powder resistivity measurement system. The results are shown in Table 1.
[0086] Table 1 Test results of electrical conductivity of silicon composite materials and silicon materials
[0087]
[0088] From the analysis of Table 1, we can see that a) by using a single layer of Nb 2 S 2 C coating can increase the conductivity of silicon oxide, silicon and silicon carbide by 4, 1 and 2 orders of magnitude respectively, and with the addition of Nb2 S 2 As the amount of C coating increases, the conductivity will gradually increase, which effectively proves that Nb 2 S 2 The coating of C can significantly improve the conductivity of the silicon negative electrode.
[0089] 3. Charge and discharge test
[0090] Take the silicon composite materials prepared in Examples 1 to 5, and the silicon materials, conductive carbon black and polyvinylidene fluoride (PVDF) prepared in Comparative Examples 1 to 3, grind and mix them evenly in a mass ratio of 7:2:1, add an appropriate amount of N-methylpyrrolidone (NMP) to make a slurry, and then coat the slurry on copper foil respectively, and dry it in a drying oven at 110°C for 10 hours; then cut it into pieces to make lithium-ion battery negative electrodes. The above-prepared lithium-ion battery negative electrodes were assembled into button batteries respectively, and the electrochemical performance was tested. The charge and discharge test of the button battery was carried out on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd. The parameter conditions were set as: normal temperature conditions, 0.3C constant current charging, 0.5C / 1C / 2C / 5C / 10C constant current discharge, and the charge and discharge voltage was limited to 0.005~2V. The test results are shown in Table 2.
[0091] Table 2 Test results of reversible capacity and discharge percentage of silicon composite materials and silicon materials
[0092]
[0093] From the reversible capacity data analysis obtained in Table 2, it can be seen that although the single-layer Nb 2 S 2 C and Ta 2 S 2 The reversible capacity of C itself is lower than that of silicon, silicon carbide and silicon oxide, but due to Nb 2 S 2 C and Ta 2 S 2 C itself has a certain lithium storage capacity, so Nb is coated on the surface of silicon, silicon carbide and silicon oxide. 2 S 2 The specific capacity of the composite material after C still remains at a high level, and there is a lot of room for application. After the silicon composite materials prepared in Examples 1 to 5 are discharged at 0.5C at room temperature, the reversible capacity is above 1000mAh / g, showing excellent lithium storage performance, thereby proving that the silicon composite material of the present invention has the advantage of high energy density.
[0094] From the analysis of the discharge percentage data obtained from Table 2, it can be seen that the discharge percentage of the silicon composite materials prepared in Examples 1 to 5 is significantly improved compared with that of Comparative Examples 1 to 3, which proves that the Nb 2 S 2 C and Ta 2 S 2 After C is coated on the silicon substrate, the rate performance of lithium-ion batteries can be rapidly improved, and with the increase of Nb 2 S 2 The increase of C coating amount makes the rate performance improve more obviously. The reason is: due to the single layer Nb 2 S 2 The interlayer spacing of C itself is large, so after being compounded with the silicon substrate, it can be used as the negative electrode material of lithium-ion batteries to facilitate the rapid release and embedding of lithium ions. 2 S 2 C and Ta 2 S 2 The coating of C can quickly improve the rate performance.
[0095] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present application. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present application. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed in the present application shall still be covered by the claims of the present application.
Claims
1. A method for preparing a silicon composite material, characterized in that: The following steps are involved: The compound is dissolved in a solvent, subjected to ultrasonic treatment, then added to a substrate, and dried to obtain an intermediate; The intermediate is placed in an inert atmosphere, heated at 700-1200° C. for 0.5-6 hours, and cooled to obtain a silicon composite material; The silicon composite material comprises a substrate, the surface of which is coated with a compound; The substrate is selected from silicon dioxide, and the compound is a single layer of Nb2S2C and / or Ta2S2C.
2. The method for preparing the silicon composite material according to claim 1, characterized in that: The mass ratio of the compound to the substrate is 0.1:99.9~3:
17.
3. The method for preparing the silicon composite material according to claim 1, characterized in that: The particle size of the substrate is between 2 and 800 nm.
4. The preparation method according to claim 1, characterized in that: The intermediate is heated in an inert atmosphere at a temperature of 800° C. for 3.5 hours.
5. The preparation method according to claim 1, characterized in that: The ultrasonic treatment time is 0.5-6 hours; the drying temperature is 80°C-200°C.
6. The preparation method according to claim 1, characterized in that: The solvent is selected from one or more of deionized water, anhydrous ethanol, acetone, dimethylformamide and tetrahydrofuran.
7. The preparation method according to claim 1, characterized in that: The inert gas in the inert atmosphere is selected from one or more of nitrogen, helium, argon and hydrogen.
8. Use of the silicon composite material obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The silicon composite material is used as the negative electrode material of a lithium ion battery.
Citation Information
Patent Citations
Preparation of high-energy graphene negative electrode material
CN107394185A